Kayuagung Duta's Social Struggle: Implementation of Pancasila Values in Social Life - Citra Lidiawati; Dasim Budimansyah; Cecep Darmawan; Susan Fitriasari (JED (Jurnal Etika Demokrasi), 2024)
This research aims to analyze the Pancasila values reflected in the social struggles of Kayuagung duta. The research method used is a Case Study. The research approach employed is qualitative. This study was conducted in the city of Kayuagung, Ogan Komering Ilir, South Sumatra, Indonesia. The informants in this study comprised 21 individuals, including current and former Duta, experts in Pancasila Ideology, community members familiar with the duta, family members of the duta, criminal law experts, religious scholars, and students. Based on the research results and discussion, it is concluded that Kayuagung duta, in their social struggles, reflect and apply the values of Pancasila in their daily lives, both in their professional duties as a Kayuagung duta and in everyday life. This is evident in their activities, which include fulfilling their religious obligations, actively participating in social activities in their local communities, engaging in communal work, practicing deliberation before making decisions, and providing assistance to others regardless of status.